Pengembangan Model Permainan untuk Pembelajaran Teknik Dasar Bola Basket di SMP Kota Medan - Muhammad Taufik Saputra; Muhammad Wisnu (INSPIRETECH GLOBAL INSIGHT & (ISORI KAMPAR), 2024)
The purpose of this study was to develop and evaluate the effectiveness of game models in teaching basic basketball skills at the junior high school level. Using the research and development (R&D) method, this study produced three innovative game models designed to improve dribbling, passing and shooting skills. The study involved 60 junior high school students (30 boys and 30 girls) aged 12-14 years. The results showed a significant improvement in the mastery of basic techniques (p < 0.05) and increased student motivation to learn basketball. The developed game model proved to be effective in improving students' motor skills and active participation, offering an attractive alternative to conventional teaching methods.